"CHARITABLE DONATION SOFTWARE FOR ANÁPOLIS: BRIDGING SOLIDARITY AND LOCAL NEEDS” (CIPEEX, 2024)
In response to the growing need to facilitate and promote the practice of donations in the city of Anápolis, Goiás, an innovative charitable donation software will be implemented. This system was developed with the aim of efficiently connecting donors to institutions and individuals in need, optimizing the distribution of resources, and strengthening the community's social fabric. The software features a user-friendly interface, accessible through mobile devices and computers, allowing donors to find and support causes of their interest. Users will have the possibility to explore local organizations, their projects, and specific needs, facilitating informed decision-making about where and how to contribute. Moreover, the software will seamlessly integrate with local charitable organizations, simplifying communication and coordination between stakeholders. Governmental bodies and local charity institutions will be invited to collaborate and provide updated information regarding community needs. The implementation of this software marks a significant stride towards promoting a culture of giving in Anápolis, fostering solidarity and collaboration for the collective well-being. By effectively connecting donors with organizations and causes, the software aims to enhance the efficiency of humanitarian assistance and contribute to the development of a fairer and more compassionate society.
Keywords: donation; community; charitable; user-friendly